Optimalisasi Instrumen Keuangan Sosial Islam dan Fintech Syariah dalam Pengentasan Kemiskinan dan Pembangunan Ekonomi - Ilham Rakha Aldias Ramadhan; Mohammad Setiawan Budi; Irman Nofal; Nurhasyim; Natasya Putri (Jurnal Ilmiah Ekonomi Islam, 2026)
This study examines the effect of zakat and sharia fintech on poverty in Indonesia. The study employs a quantitative approach using quarterly time-series data from 2015Q1 to 2025Q4. Data were analyzed using multiple linear regression supported by stationarity and cointegration tests. Poverty is the dependent variable, while zakat and sharia fintech are independent variables. The results show that both zakat and sharia fintech have a negative and significant effect on poverty. The findings indicate that zakat contributes to poverty reduction by redistributing income and empowering individuals. At the same time, sharia fintech supports financial inclusion by expanding access to financial services and financing opportunities, particularly for micro, small, and medium enterprises (MSMEs). Furthermore, the cointegration test confirms the existence of a long-term relationship among the variables. These results highlight the importance of integrating Islamic social finance and digital financial innovation to support sustainable poverty reduction in Indonesia.